Radiodensity of Various Dental Biomaterials for Endodontics: The Role of Particle Size - Mohammad Ali Saghiri; Steven M Morgano; Hamed Kazerani; Shuying Jiang; James L Gutmann; Kasra Momeni; Franklin Garcia Godoy (Journal of Clinical and Diagnostic Research, 2020)
Introduction: The thickness threshold for detecting endodontic biomaterials depends on many factors, such as the nature of the radiopacifier and the particle size. Aim: The aim of this study was to determine the effect of thickness on radiodensity of various endodontic biomaterials; and evaluate the impact of radiopacifier particle size on radiodensity. Materials and Methods: This in-vitro study was conducted between August 2018 to December 2019. The study was divided in two parts, in first part, Six endodontic biomaterials (AH26, EndoSequence, Endoseal Mineral Trioxide Aggregate (MTA), Nano-MTA, Endocem Zr, and MTA without radiopacifier) were selected and evaluated in different thicknesses, in second part, MTA mixed with Bismuth oxide 10 μm, 200 μm, 120 nm (Groups 1-3), and Zirconium oxide 5 µm, 1 µm and 20 nm (Groups 4-6) were placed in frames with 1 mm, 0.5 mm, 0.2 mm, 0.1 mm thicknesses to evaluate the radiopacity. Results: The mean radiodensity was significantly different among various thickness (p<0.001) and materials (p<0.001). The changes of the radiodensity in various thickness from one material to the other were not uniform (interaction p-value <0.001). A 1 mm thickness had highest radiodensity (206.6±83.99), followed by 0.5 mm (68.9±24.6), 0.2 mm (17.9±4.9), and 0.1 mm thick material had least radiodensity (11.97±4.37). Materials of AH26 (99.1±103.2), Nano MTA (97.4±104.9), Endoseal MTA (87.86±101.4), Endosequence BC sealer (85.5±93.87) and Endocem Zr (71.88±77.67) were significantly different from the control group (16.38±10.85). The size of particles played important role in radiodensity (p<0.001). The radiodensity of Fine GIII (100 nm) material (112.68±108.47) was significantly higher than other materials: Thin GII (200 nm) (100.9±102.4), Fine GVI (20-40 nm) (99.7±95.1), Coarse GI (10 μm) (76.66±74.75), Thin GV (1~3 µm) (63.19±67.3), Coarse GIV (5 μm) (49.66±51.59) and MTA without Radiopaque Agent GVII (100%) (23.67±19.68). The effect of the thickness on radiodensity was different for each biomaterial, with significant differences from the control group. Conclusion: One of the readily available methods for increasing radiodensity is to increase the amount of radiopacifier, which might compromise the physical properties of the material. Fine particle radiopacifier (120 nm) with 1 mm thickness has significantly higher radiodensity than any other biomaterials in this study. Within the limitations of the current study, it can be concluded that the radiopacifier particle size has a significant impact on the level of radiodensity of dental biomaterials. Finding the optimum distribution, size, and geometry of radiopacifier particles within the same fraction rate can enhance the radiodensity.